Illuminating the norepinephrine transporter: fluorescent probes based on nisoxetine and talopram. Issue 7 (9th June 2021) - Camacho-Hernandez, Gisela Andrea; Casiraghi, Andrea; Rudin, Deborah; Luethi, Dino; Ku, Therese C.; Guthrie, Daryl A.; Straniero, Valentina; Valoti, Ermanno; Schütz, Gerhard J.; Sitte, Harald H.; Newman, Amy Hauck
Abstract : A nisoxetine-based fluorescent probe, 6, has been synthesized that can be used to visualize the norepinephrine transporter (NET) in NET-expressing HEK293 cells at low nanomolar concentrations. Abstract : The utilization of fluorescent ligands to study the monoamine transporters (MATs) has increased our knowledge of their function and distribution in live cell systems. In this study, we extend SAR for nisoxetine and talopram as parent compounds, to identify high affinity rhodamine-labeled fluorescent probes for the norepinephrine transporter (NET). Nisoxetine-based fluorescent probe 6 demonstrated high binding affinity ( K i = 43 nM) for NET and an overall selectivity compared to the other transporters for dopamine (DAT; K i = 1540 nM) and serotonin (SERT; K i = 785 nM) in competitive radioligand binding assays. Using confocal microscopy, compound 6 was shown to stain both NET and SERT, but not DAT, at low nanomolar concentrations, in transporter-expressing cells.